Novel Histopathological Findings of Micro Bone Fragments and Epithelial Response in the Oral Mucosa in Bisphosphonate-Related Osteonecrosis of the Jaw - Gaku Koizumi DDS; Akinobu Hayashi MD, PhD; Akira Takigawa DDS; Rina Yamada DDS; Taku Murata DDS, PhD; Kasumi Shimizu DDS, PhD; Masatoshi Watanabe MD, PhD; Naoya Arai DDS, PhD (SAGE Publishing, 2024)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) occurs in the jawbone and interfacing oral mucosa of patients treated with bisphosphonates. Herein, we report novel histopathological findings in the oral mucosa of a surgical specimen obtained from a 61-year-old man with BRONJ. The resected jawbone and adjacent oral mucosa were separated for histological examination. The mucosal tissue was examined using Von Kossa staining and immunohistochemical (CK5/6, p63) staining of non-decalcified paraffin sections. Pseudoepitheliomatous hyperplasia (PEH), a microscopic feature of the mucosal epithelium in BRONJ, was observed in soft tissue specimens, concomitant with inflammatory cell infiltration. Von Kossa staining revealed small fragments of necrotic bone, tens to hundreds of micrometers in size, scattered within the connective tissues; the PEH forefront contacted some of the bone fragments. Immunohistochemical staining demonstrated that occasionally, the PEH not only contacted but also encompassed the bone fragments. To our knowledge, this is the first report of presence of micro bone fragments and their association with PEH in the oral mucosa in BRONJ.